Elizabeth Bishop and Marianne Moore : The Psychodynamics of Creativity - Diehl, Joanne Feit, 1947- (Book collections on Project MUSE., 1993)
This highly innovative work on poetic influence among women writers focuses on the relationship between modernist poet Elizabeth Bishop and her mentor Marianne Moore. Departing from Freudian models of influence theory that ignore the question of maternal presence, Joanne Diehl applies the psychoanalytic insights of object relations theorists Melanie Klein and Christopher Bollas to woman-to-woman literary transactions. She lays the groundwork for a far-reaching critical approach as she shows that Bishop, mourning her separation from her natural mother, strives to balance gratitude toward Moo.